Effects of RAAS blockade on acute kidney injury in head and neck cancer patients post-chemoradiotherapy - Yi-Ting Chen; Yao-Hung Kuo; Chih-Feng Lin; Chun-Wei Wang; Chiao-Ling Tsai (BMC Nephrology)
Abstract Background The incidence of acute kidney injury (AKI) is high among head and neck cancer (HNC) patients following Platinum-based concurrent chemo-radiotherapy (CCRT). However, the effect of renin-angiotensin-aldosterone system (RAAS) blockade on the risk of AKI in HNC patients undergoing CCRT is controversial. This study aimed to investigate the association between RAAS blockade, AKI and survival in HNC patients undergoing CCRT. Method This retrospective cohort study included 989 HNC patients treated between January 2016 and July 2022, with follow-up extending to July 2022. Among them, 65 (6.6%) patients were using RAAS blockade for hypertension control, while 924 were non-users. Clinical data and demographics were retrieved. Cox regression models were employed to analyze primary outcomes, including AKI and patient survival. Results There were 65 (6.6%) patients being RAAS blockade users in the study. The mean age of RAAS blockade users was older than that of non-users (61 vs. 55 years old, p < 0.001). Overall, 219 (22.1%) patients developed AKI, including 25 RAAS blockade users. RAAS blockade users had a higher risk of AKI compared to non-users (38% vs. 21%, p = 0.001) and also had a worse mortality rate (35% vs. 22%, p = 0.015). Factors such as male gender, age, RAAS blockade usage, and baseline serum creatinine levels independently predicted the onset of AKI and patient survival. Conclusion RAAS blockade users developed AKI, which significantly predicted patient survival. Diligent post-CCRT renal function monitoring and hydration in RAAS blockade users are crucial to mitigate AKI risk and potentially improve survival in this patient group.